2019
DOI: 10.18502/kms.v5i1.3958
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Phase Composition of V-Al-N-C Master Alloy

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…46 In another study, high dispersity enabled the conformational changes of the brushes, resulting in a hysteretic hydration response as a function of pH. 47 Brush thickness has also been found to alter the macroscopic wettability of zwitterionic polymers driven by brush chain associations. 11,48 Palai et al have found through machine learning importance analysis that brush thickness and density are highly important parameters toward protein adsorption.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…46 In another study, high dispersity enabled the conformational changes of the brushes, resulting in a hysteretic hydration response as a function of pH. 47 Brush thickness has also been found to alter the macroscopic wettability of zwitterionic polymers driven by brush chain associations. 11,48 Palai et al have found through machine learning importance analysis that brush thickness and density are highly important parameters toward protein adsorption.…”
Section: ■ Conclusionmentioning
confidence: 99%